Peran Komunikasi Lintas Budaya dalam Membangun Keharmonisan Antar Santri: Studi Kasus Pesantren Life Skill Daarun Najaah - Heru Sofyan (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2023)
This study aims to explain the role of cross-cultural communication in building harmony between students. This study uses a qualitative phenomenological approach. Data collection techniques by means of interviews and field observations. The informants are students of the Daarun Najaah Lift Skill Islamic Boarding School who are ethnically outside Java. The number of informants consisted of 5 students of Sumatran and Sulawesi ethnicity. The results of this study have three results, namely in building harmony requires learning language and culture, adaptation or self-adjustment, and understanding the meaning of verbal and non-verbal symbols. Learning language and culture is the key to producing effective or harmonious communication relationships. With the same language when communicating, the interaction will be successful. Adaptation or self-adjustment is the initial stage of the individual to try to create new strategies in interacting in a new environment. Then understanding the meaning of verbal and non-verbal is the next way to simplify and reduce barriers to communication.